Pelaksanaan Tanggung Jawab Sosial Perusahaan (Corporate Social Responcibility/CSR) pada PT. Transportasi Jakarta - ; Elizabeth (Syntax Idea)
Every company not only has a responsibility to increase the income and welfare of its employees but also has a responsibility to the community and the environment where it carries out its business. With social responsibility, the Company can make one of the Company's contributions to improving the economy while also preserving the environment in order to improve the welfare of the surrounding community. Corporate Social Responsibility is an organic relationship between companies, increasing profits and developing social activities. Corporate Social Responsibility is not only limited to the environment and society but all related parties, either directly or indirectly. The purpose of this research is to determine the implementation of Corporate Social Responsibility (CSR) at PT.Transportasi Jakarta towards the community. The research method used is empirical normative legal research using conceptual, statutory and sociological approaches. The results of the research show that PT.Transpotasi Jakarta has been implemented quite well even though there are no government regulations that require the implementation of Corporate Social Responsibility, so there should be regulations related to the implementation of CSR that regulate the planning, implementation and supervision of corporate social responsibility.